Pembelajaran Sentra dalam Membangun Kecerdasan Jamak di Sekolah Dasar - Maharani Ramadhanti; M. Syarif Sumantri; Edwita Edwita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
This study aims to find multiple intelligences in learning centers in primary schools. This research was conducted in MI Plus Tangerang city Asy-Syukriyyah with 14 students from class 1 B as research subjects. The reason for the chosen subject is because the class is unique and needed special holding. This study uses qualitative methods and for the research methods to follow the research flow for the advancement of Spradley. The process of collecting data uses observation, interviews, and document analysis, while data analysis consists of: domain analysis, taxonomic analysis, and analytical themes. The results showed that the multiple intelligences obtained in the learning of MI Plus Asy-Syukriyyah center include: linguistic intelligence, logic-mathematical, spatial, interpersonal, intrapersonal, kinesthetic, and naturalist. Conclusion is learning center in MI Plus Asy-Syukriyyah building multiple intelligences intelligence, intelligence built between intelligence: interpersonal, naturalist, intrapersonal, spatial, kinesthetic, music, linguistic and logical mathematical. Keywords: BCCT Learning, Multiple Intelligences, Elementary School